Battery energy storage system integration to the more electric aircraft 270 V DC power distribution bus using peak current controlled dual active bridge converter - Mohd Tariq (2018)
The electrical power requirement of the aircraft has increased due to the secondary loads becoming electrical. This has led to the deployment of high energy density battery (Lithium-based batteries) in the MEA. In this paper, a high energy density battery (lithium-iron phosphate `LiFePO4') is used as the battery energy storage system (BESS). The function of the BESS is to start the engine starter-generator set of the MEA and to provide the transients and emergency loads. The dual active bridge (DAB) dc-dc bidirectional converter is used as the charger circuit for the BESS. The 270 V dc based power distribution network is used in the more electric aircraft (MEA). The BESS is integrated to the MEA 270 V dc power distribution bus using the DAB converter. Since, the BESS has to provide the transients/peak load, the fast dynamic response is required for the DAB converter. The coupling inductor current in the DAB converter is ac and has a peak value. In this paper, a peak current controller is proposed for the integration of the BESS to the MEA 270 V dc power distribution bus. The proposed control provides a limit on the peak current as well as it gives fast transient response. The advantages of using the proposed peak current control on avoiding the saturation of the high frequency transformer core is also reported in the paper. The proposed controller for the DAB converter along with the BESS is designed with respect to the MEA environment and is verified with the simulation results in the PSim simulation environment.